1996
DOI: 10.1093/carcin/17.8.1633
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced genomic instability and persisting oxidative stress in primary bone marrow cultures

Abstract: There is accumulating evidence that cells exposed to low and often environmentally relevant doses of ionizing radiation survive the initial insult, but transmit genomic instability to their progeny. The underlying mechanism of radiation-induced genomic instability is unknown. We present bio-chemical evidence consistent with the hypothesis that enhanced and persistent oxy-radical activity may be responsible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
103
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(117 citation statements)
references
References 10 publications
12
103
1
1
Order By: Relevance
“…The data in Kadhim et al (1997) and suggest that genetic factors leading to expression of chromosomal instability may be counteracted by other factors, which cause a long-term programmed cell death response to radiation. The data in this paper, showing that ICCM is able, in the long-term, to induce ROS, which was shown by Clutton et al (1996) to lead to chromosomal instability, and also to initiate the apoptotic cascade, means that the signal produces a response in cells which can lead to death or to persistence of damage. The fate of the cell and ultimately, the tissue or organism, may well be determined by the genetic make-up of the individual and …”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The data in Kadhim et al (1997) and suggest that genetic factors leading to expression of chromosomal instability may be counteracted by other factors, which cause a long-term programmed cell death response to radiation. The data in this paper, showing that ICCM is able, in the long-term, to induce ROS, which was shown by Clutton et al (1996) to lead to chromosomal instability, and also to initiate the apoptotic cascade, means that the signal produces a response in cells which can lead to death or to persistence of damage. The fate of the cell and ultimately, the tissue or organism, may well be determined by the genetic make-up of the individual and …”
Section: Discussionmentioning
confidence: 75%
“…Changes in the expression of oxidative stress also persisted. Both oxidative stress and miochondrial abnormalities have been suggested as important factors in the production of persistent, nonclonal genomic instability in cells (Clutton et al, 1996). This group showed that irradiated cells that survive have a persistently elevated production of toxic oxygen radicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue/cells at treatment site (including tumor-associated endothelial cells, normal tissue and remnant cancer cells) that initially survive irradiation may elicit factors. These factor(s) may transduce and alter the physiology of the neighboring bystander cells [18][19][20][21][22] by paracrine feedback signaling that may pre-dispose the cells to carcinogenic processes [23] in normal tissue, and tumor cell growth in surviving cancer cells leading to tumor recurrence at later time. Reports from our laboratory demonstrated that radiation at doses used in fractionated radiotherapy could selectively induce the DNA-binding activity of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) [24][25][26] and the occurrence of a positive feedback loop between tumor necrosis factor-alpha (TNF-α) and NF-κB.…”
Section: Bystander Effectmentioning
confidence: 99%
“…Furthermore, genomic instability is thought to be mediated via bystander mechanisms (43). Bystander effects have been shown to be mediated by gap-junction intercellular (GJIC) communication (41,44,45) and by signaling via diffusible secreted factors (46,47).…”
Section: Bystander Effectsmentioning
confidence: 99%